Efficiency of IL-6 in Early Prognosis and Follow-Up in Critically Ill Patients with Septic Shock - Yenifer Gamarra-Morales; Jorge Molina-López; Felipe-Carlos Santiago-Ruiz; Lourdes Herrera-Quintana; Héctor Vázquez-Lorente; Félix Gascón-Luna; Elena Planells (Diseases)
Background/Objectives: The aim of this study was to investigate the response of interleukin-6 (IL-6) during the first few hours of a patient’s stay in the Intensive Care Unit (ICU) in a sample of critically ill patients with septic shock, compared to healthy subjects as controls. Additionally, the study examined the association of IL-6 with morbidity and mortality in these patients, as well as its relationship with biomarkers such as lactic acid, C-reactive protein (CRP) and procalcitonin (PCT). Methods: This was a prospective analytical study involving 28 critically ill patients with septic shock, monitored from ICU admission through to their first three days of stay. Demographic data, comorbidities and clinical information, including IL-6 and severity scores, were recorded. Results: IL-6 levels were significantly higher in patients with septic shock compared to healthy subjects (p < 0.001) upon admission. IL-6 levels decreased by the third day of ICU stay (p < 0.005). An association between IL-6 and mortality was observed (areas under the curve 0.826, confidence interval (CI) 95% 0.659−0.994, p < 0.008). Significant correlations between IL-6 and lactic acid (p < 0.009 and p < 0.018) and partial thromboplastin time (p < 0.004 and p < 0.007) were found on the first and third days, respectively. IL-6 was also the correlated with an anion gap at admission to the ICU (p < 0.009). Conclusions: In conclusion, this study suggests that IL-6 could be a valuable marker for early sepsis follow-up in ICU patients, particularly during the first 72 h of hospitalization, providing important prognostic information in patients with septic shock.